PERSEPSI GURU BIOLOGI DAN SISWA SMA NEGERI SE-KOTA PEKANBARU TERHADAP KUALITAS BUKU PELAJARAN BIOLOGI SMA/MA KELAS X TERBITAN ERLANGGA BERBASIS KURIKULUM 2013 - Suci Indah Permata Sari Indah Permata Sari; Mariani Natalina Mariani Natalina; Darmadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this study was determine the perception of Biology teachers and Public Senior High School students in Pekanbaru to the quality of Biology textbook for Senior High School class X published by Erlangga based on Curriculum 2013. This study was conducted from January to June 2014. Sample in this study were 6 Biology teachers who taught in class X and 274 Public Senior High School students class X majors MIA (Matematika dan Ilmu Alam) in Pekanbaru who became target the implementation of Curriculum 2013, whose chosen by purposive sampling technique. Data collection instruments was questionnaires, which grouped into teacher questionnaire and student questionnaire. Teacher questionnaire consists of the closed-ended questionnaire was 50 statments and divided into 5 indicators, the indicators are component of feasibility content, component of material presentation, component of language, component of book graph, component of compatibility with Curriculum 2013. The open-ended questionnaire was 5 questions. Student questionnaire consists of the closed-ended questionnaire was 26 statments divided into 4 indicators, the indicators are component of feasibility content, component of material presentation, component of language, component of book graph. Data analyzed descriptively. Overall, the quality of Biology textbook based on Biology teachers perception showed in quite well criteria with average of 2,54 and based on students perception showed quite well criteria with average 2,43. This indicate the textbook have not been able to complete all criteria that has been established by BSNP (Badan Standar Nasional Pendidikan).Key Words: Perception, Quality of Biology Textbook, Curriculum 2013